SEED PHYSICAL SCARIFICATION AND GROWING MEDIA ON VIGOR OF Moringa oleifera - Ubaidillah, -; Zulaiha, A. V.; Dianita, R. (Pastura, 2020)
This experiment was aimed to reveal the effect of seed physical scarification and various growing media on vigor of Moringa oleifera. This study was conducted in greenhouse and consisted of two phases of experiment; first was studied the effect of physical scarification on seed germination of M. oleifera and the second was studied the effect of seed physical scarification and various sub optimum growing media on vigor of M. oleifera. The germination test was arranged in randomized completely design with 4 treatments that were P0 = non scarification, P1 = one side scarification, P2 = two sides scarification, and P3 = full side scarification. The variables measured were germination percentage (%) and seedling dry weight (g/plant). The second study was arranged in a factorial randomized completely design with the four treatments of scarification (P0, P1, P2 and P3) over six growing media (sands, bricks, bricks and sands mixture, bricks and soils mixture, soils and sands mixture, and soils). The variables observed were petioles number, plant height (cm/plant), and plant dry weight (g/plant). The scarification was significantly affect (P<0.05) the germination percentage and seedling dry weight. Scarification and growing media also affected the vigor of M. oleifera significantly (P<0.05). Two side seed scarification improve the germination and seedling dry weight instead of control. Combination of scarification in two sides and growing media of soils and sands mixture given the highest vigor of M. oleifera reflected on petioles number, plant height, and plant dry weight. Keywords: germination, M. oleifera, scarification, sub optimum media, vigor